MODERASI ISLAM MUHAMMADIYAH DENGAN RISALAH ISLAM BERKEMAJUAN DI MINANGKABAU - Aini, Quratun Aini (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2025)
Minangkabau is one of the regions in Indonesia known for its strong Islamic religious traditions that are closely intertwined with customary values. However, in the development of modern society, social, political, and cultural dynamics often give rise to new challenges to maintaining the balance between tradition, religion, and national values. One organization that plays an important role in promoting religious moderation in Minangkabau is Muhammadiyah. The purpose of this study is to examine how Muhammadiyah contributes to the success of religious moderation in Minangkabau. This research employs a descriptive qualitative method with a library research approach. Data were collected from relevant articles and academic journals. Several efforts undertaken by Muhammadiyah to promote religious moderation in Minangkabau include: (1) calls and appeals from Muhammadiyah leaders regarding religious moderation; (2) efforts in the field of education through schools and higher education institutions that are open to followers of all religions; (3) social and humanitarian activities through various humanitarian aid programs without regard to religious affiliation; (4) the use of social media and print media; and (5) interfaith forums. The concept of moderation from Muhammadiyah’s perspective consists of several aspects. First, in the realm of faith (ʿaqīdah) and worship (ʿibādah), Muhammadiyah emphasizes the importance of deep, balanced, and comprehensive internalization, so that faith is not merely symbolic and worship does not stop at ritual practices alone. Second, in terms of morality (akhlak), Muhammadiyah believes that emulating the Prophet Muhammad should not be limited to outward attributes, but must be manifested in good moral conduct (ḥasanah). Third, in the area of social relations (muʿāmalah), Muhammadiyah adopts a progressive and dynamic stance, adapting Islamic teachings to the demands of the times without abandoning the principles of Islamic law (sharia).